2023
DOI: 10.3390/ani13061061
|View full text |Cite
|
Sign up to set email alerts
|

Dog Owners’ Attitude toward Veterinary Antibiotic Use and Antibiotic Resistance with a Focus on Canine Diarrhea Management

Abstract: An ad hoc questionnaire was designed in order to investigate AMR knowledge amongst Italian dog owners, owner expectations concerning pharmacological treatment of canine AD, and client attitudes towards and compliance with alternative strategies to antimicrobial administration. A total of 250 questionnaires were returned. Most of respondents were female, aged 36–70 and workers. More than a half of participants owned one dog with mixed breed, with Labrador retriever, golden retriever, dachshund, and border colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(75 reference statements)
1
1
0
Order By: Relevance
“…Diarrhea was the most frequently cited reason for antibiotic administration in dogs in the present study. This is consistent with previous studies that also identified gastrointestinal or intestinal disease as a frequent indication for antibiotic administration [28,29]. However, current studies and guidelines state that there is no indication for the usage of antibiotics in acute uncomplicated diarrhea without evidence of systemic inflammation or sepsis [30][31][32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 89%
“…Diarrhea was the most frequently cited reason for antibiotic administration in dogs in the present study. This is consistent with previous studies that also identified gastrointestinal or intestinal disease as a frequent indication for antibiotic administration [28,29]. However, current studies and guidelines state that there is no indication for the usage of antibiotics in acute uncomplicated diarrhea without evidence of systemic inflammation or sepsis [30][31][32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 89%
“…Antibiotics are commonly used to treat pet diseases, and indeed significantly improve pet health. However, antibiotic abuse is not uncommon, especially when seeking to treat bacterial infections [ 2 ]. Such abuse can trigger bacterial antibiotic resistance, and excessive dosages can disrupt the intestinal floral balance, rendering pets prone to constipation, diarrhea, and other gastrointestinal diseases that seriously endanger their health [ 3 ].…”
Section: Introductionmentioning
confidence: 99%